Logistics as a key element of crisis management - Boratyn, Dominik; Maniek, Marcin; Kędra, Andrzej; Sroślak, Grzegorz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Nowadays, logistics plays a special role in almost all spheres of social and economic life. Logistics is the foundation for the functioning of numerous public and private entities, such as the army, health care facilities and the entire food industry. Without logistics and related activities, such institutions would not be able to fully implement the tasks entrusted to them, and this would consequently threaten to destabilize the normal functioning of the state. We can therefore notice that in the modern world, logistics plays a fundamental role. Moreover, it is even more visible in unusual situations, i.e. crisis situations, which pose a challenge to public, private and social institutions. The aim of this article is to present the importance of logistics in the crisis management system. The author will focus on discussing the existing research related to this topic, and will also indicate his own observations, the aim of which will be to verify the adopted research hypothesis assuming that logistics plays a special role at all stages (phases) of crisis management.